2020
DOI: 10.3390/rs12040678
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Satellite Precipitation Estimates over Australia

Abstract: This study evaluates the U.S. National Oceanographic and Atmospheric Administration’s (NOAA) Climate Prediction Center morphing technique (CMORPH) and the Japan Aerospace Exploration Agency’s (JAXA) Global Satellite Mapping of Precipitation (GSMaP) satellite precipitation estimates over Australia across an 18 year period from 2001 to 2018. The evaluation was performed on a monthly time scale and used both point and gridded rain gauge data as the reference dataset. Overall statistics demonstrated that satellite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…It was consistent with the other "best-performing" datasets-the ERA-Interim (ERA-INT) and Global Precipitation Climatology Centre (GPCC) reanalyses [3]. Studies have indicated that significant degradation of performance occurs over elevated topography, particularly during winter where snow and cold surface contamination can become an issue [9,14]. This is a concern given the significant presence of mountainous terrain on the PNG mainland, though the effect of snow and cold surface contamination is only a minor issue confined to the highest peaks of the country.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…It was consistent with the other "best-performing" datasets-the ERA-Interim (ERA-INT) and Global Precipitation Climatology Centre (GPCC) reanalyses [3]. Studies have indicated that significant degradation of performance occurs over elevated topography, particularly during winter where snow and cold surface contamination can become an issue [9,14]. This is a concern given the significant presence of mountainous terrain on the PNG mainland, though the effect of snow and cold surface contamination is only a minor issue confined to the highest peaks of the country.…”
Section: Introductionsupporting
confidence: 79%
“…The gridded comparison demonstrated that the errors in satellite precipitation estimates across PNG can be large in some areas, especially over the mountainous regions. The poor performance of satellites over topography has been shown in earlier studies [9,14]. Cold surface contamination is unlikely to be the source of these large biases over PNG's topography as snow only falls on the highest peaks in PNG and it would lead an overestimation of rainfall rather than the underestimation observed.…”
Section: Validation Studymentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, the CMORPH Blended (CMORPH-BLD) product which further incorporates gauge data through optimal interpolation was selected for evaluation. CMORPH-BLD has been shown to be more accurate than the gauge-corrected product CMORPH-CRT, over regions where a dense gauge network exists [27], though performance was similar when gauge density is low such as, for example, over PNG [28].…”
Section: Datasetsmentioning
confidence: 99%
“…Further, they showed that the zonal mean of precipitation extremes greatly differed and had biases among datasets. Chua et al [14] validated the U.S. National Oceanographic and Atmospheric Administration (NOAA) Climate Prediction Center morphing technique (CMORPH) ( [15]) and the GSMaP over Australia, and demonstrated that satellite precipitation estimates exhibited good skills over Australia and that the skill of satellite precipitation estimates was highly dependent on rainfall intensity. Therefore, detecting precipitation extremes by using satellite-derived precipitation products requires an understanding of the characteristics of the product being used and an examination of a suitable method of detection.…”
Section: Introductionmentioning
confidence: 99%